A Rhetorical study in the poetry of the Abbasid era - Al-Bayati, Eilaf (Al-Adab Journal, 2025)
This article aimed to study poetry in the Abbasid era across all four periods. It employed a descriptive methodology, drawing on previous studies of Abbasid and Arabic poetry, and a qualitative analytical approach to analyze poetic samples from several Abbasid poets. The studied poets included Al-Mutanabbi, Abu Al-Faraj Al-Hamadani, Ibn Al-Rumi, Abu Al-Atahiya, Bashshar ibn Burd, Al-Sharif Al-Murtada, Mahyar Al-Daylami, Al-Khabbaz Arzi, Khashajim, Ibn Anin, and Sari’ al-Ghawwani. The results indicate that Abbasid poets utilized a diverse range of rhetorical techniques and poetic devices to create rich and meaningful imagery. They adeptly employed metaphor and allegory to embody ideas and emotions, while using symbolism to express philosophical, religious, and social concepts. Furthermore, they demonstrated an ability to evoke mystery and complexity in their poetic texts, enhancing the depth of their poems and making them conducive to contemplation and reflection across time. Additionally, the study revealed that Abbasid poets were influenced by the context of their era and the social and cultural conditions they experienced, with these circumstances closely tied to the content and stylistic approaches they employed in their poetry.